2018
DOI: 10.1111/xen.12430
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of stakeholders’ attitudes to xenotransplantation

Abstract: The Malaysian stakeholders were cautious about xenotransplantation. This study showed that their views regarding the application are complex and multifaceted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 36 publications
(109 reference statements)
3
22
1
4
Order By: Relevance
“…Third, the lack of any standardized approach to questioning respondents regarding their opinions. For example, of the final eight articles included in the meta‐analysis, religiosity was addressed from several different perspectives: (a) one series of articles asked whether the participant was Catholic, non‐Catholic, or other ; (b) one article included four items pertaining to religiosity and moral concerns that were measured on a seven‐point Likert scale ; (c) one article used a standardized religious fundamentalism scale ; while (d) another group coded religion as yes or no without showing the form of the questionnaire item (ie, how the question was asked) . A bigger concern about the questions asked revolves around genetic engineering.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Third, the lack of any standardized approach to questioning respondents regarding their opinions. For example, of the final eight articles included in the meta‐analysis, religiosity was addressed from several different perspectives: (a) one series of articles asked whether the participant was Catholic, non‐Catholic, or other ; (b) one article included four items pertaining to religiosity and moral concerns that were measured on a seven‐point Likert scale ; (c) one article used a standardized religious fundamentalism scale ; while (d) another group coded religion as yes or no without showing the form of the questionnaire item (ie, how the question was asked) . A bigger concern about the questions asked revolves around genetic engineering.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary review of the 19 studies being considered, presented with considerable independent variable heterogeneity, and exhibited significant variability in the questions asked . However, the majority reported that, among those surveyed, >50% supported XTx, with a range from as low of 37% to a maximum of 83% . Of the 19 data‐based studies, 12 were considered for inclusion in our study, but only eight provided original data in a usable format for meta‐analysis .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on consumer behaviour have indicated that perceived benefit and risk strongly influenced individual responses regarding acceptance of technology [36][37][38][39][40][41]. Perceived benefit is a positive predictor of attitude, while perceived risk is a negative predictor of attitude.…”
Section: Perceived Benefit and Riskmentioning
confidence: 99%
“…The uptake of xenotransplantation depends on both research advancements and public approval. In Malaysia, 469 people were surveyed to predict perspectives on religion, perceived benefits, and risks, among others . Their results describe the attitudes of stakeholders involved in xenotransplantation, exemplifying the need for a multidimensional outlook …”
Section: Viewpointsmentioning
confidence: 99%